2010
DOI: 10.1212/wnl.0b013e3181d7d8cb
|View full text |Cite
|
Sign up to set email alerts
|

When, where, and how the corpus callosum changes in MCI and AD

Abstract: Callosal changes are already present in patients with amnestic mild cognitive impairment (MCI) and mild Alzheimer disease (AD). The precocious involvement of the anterior callosal subregion in amnestic MCI extends to posterior regions in mild AD. Two different mechanisms might contribute to the white matter changes in mild AD: wallerian degeneration in posterior subregions of the corpus callosum (suggested by increased axial diffusivity without fractional anisotropy modifications) and a retrogenesis process in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
138
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(160 citation statements)
references
References 41 publications
17
138
2
3
Order By: Relevance
“…Wang and colleagues [91] also reported a decreased FA value in the genu and the splenium and increased ADC in the genu of the CC (see Table 3 for technical details of the study). In our study [21], we found reduced FA in the genu and anterior body of the CC, increased DA in the body and in the posterior subregions of the CC, and increased DR in the entire CC in patients with mild AD compared with HC. We found no significant differences in the CC in patients with amnesic MCI compared with HC.…”
Section: Diffusion-weighted Imaging and Diffusion Tensor Imaging Studiessupporting
confidence: 54%
See 4 more Smart Citations
“…Wang and colleagues [91] also reported a decreased FA value in the genu and the splenium and increased ADC in the genu of the CC (see Table 3 for technical details of the study). In our study [21], we found reduced FA in the genu and anterior body of the CC, increased DA in the body and in the posterior subregions of the CC, and increased DR in the entire CC in patients with mild AD compared with HC. We found no significant differences in the CC in patients with amnesic MCI compared with HC.…”
Section: Diffusion-weighted Imaging and Diffusion Tensor Imaging Studiessupporting
confidence: 54%
“…Nevertheless, the results obtained on patients with mild AD and amnesic MCI were not supported by statistical correction for multiple comparisons. Recently, however, we replicated the study on a larger sample of patients with mild AD and amnesic MCI [21] and found a significant WM density reduction in the genu and splenium of the CC in patients with mild AD. In patients with amnesic MCI compared with HC, we found a reduction only in the genu of the CC (see Table 2 for technical details of the study).…”
Section: Voxel-based Morphometry Studiesmentioning
confidence: 56%
See 3 more Smart Citations